Effect of Hyperglycemia on Purinergic and Nitrergic Inhibitory Neuromuscular Transmission in the Antrum of the Stomach: Implications for Fast Gastric Emptying - He, Xue-Dao; Guo, Yan-Mei; Goyal, Raj K. (Frontiers in Medicine, 2018)
Background: Hyperglycemia has been reported to enhance vagovagal reflex that causes the release of inhibitory neurotransmitter, nitric oxide, at the neuromuscular junction in the antrum to relax the antrum and slow gastric emptying by stimulating glucose-sensitive afferent neurons. However, hyperglycemia has also been reported to cause fast gastric emptying that may be due to suppression of the inhibitory motor neurons. Aims: The purpose of the present study was to investigate changes in inhibitory NMT in the gastric antrum due to hyperglycemia. Methods: Inhibitory electrical junction potentials were recorded from gastric antral muscle strips, using intracellular electrodes under non-adrenergic, non-cholinergic conditions. Studies were performed in non-hyperglycemic NOD (NH-NOD), NOD mice as they develop hyperglycemia (H-NOD) and their age-matched controls. The purinergic (pIJP) and nitrergic (nIJP) were isolated pharmacologically. Results: The control pIJP was large, around -18 mV and nIJP was small, around -9mV. In NH-NOD the IJPs were not affected, but in H-NOD pIJP was nearly abolished and nIJP was significantly reduced. In H-NOD mice, membrane hyperpolarization caused by exogenous α, ß-MeATP or DNO was similar to that in WT controls (p>0.05). H-NOD smooth muscles were significantly depolarized as compared to NH-NOD smooth muscles. Conclusions: These observations show that hyperglycemia causes suppression of purinergic and nitrergic transmission by acting on the motor neurons that form the last neuron in the vagovagal circuit. Moreover, the loss the neurotransmission is due to a defect in neurotransmitter release rather than a defect in signal transduction. Hyperglycemia also causes depolarization of smooth muscles that may increase their excitability.